Promosi Wisata Berbasis Kearifan Serta Praktek Membuat Caption Dan Hastag Bernetiket Di Instagram Bertemakan “Promosi Wisata” Di Kabupaten Gianyar - ni luh putu surya astitiani astitiani (Cv. Utility Project Solution, 2022)
Preserving local culture and customs is one of the efforts to maintain local wisdom, especially when combined and further promoted with the use of technology such as understanding netiquette and creating captions and hashtags on social media. The purpose of this community service is to preserve the original culture of the local population which continues to be modernized with technological developments. The location of this community service implementation is at the Batuan Village Office, Gianyar Regency, Bali Province. The targets of this community service activity were the Yowana and Pakis youth groups of Batuan Village, Gianyar Regency, with a total of 140 offline participants and 73 online participants. The results of this activity are providing training and education on Tourism Promotion Based on Local Wisdom that Understands Netiquette and the practice of making netiquette Captions and Hastags on Instagram with the theme